Protecting the airway and the physician: Aspects of litigation arising from tracheotomy. Issue 5 (4th June 2015) - Farida, Jeremy P.; Lawrence, Lauren A.; Svider, Peter F.; Shkoukani, Mahdi A.; Zuliani, Giancarlo F.; Folbe, Adam J.; Carron, Michael A.
Abstract: Background: In recent decades, medical malpractice costs have increased and have led to a change in the way physicians practice medicine. Tracheotomies are cases in which complications have a high risk of morbidity and mortality and the potential for litigation. Methods: The Westlaw legal database was used to gather data on 43 jury verdicts and settlements from 1987 to 2013. Various factors included outcome, defendant specialty, and the reason for litigation. Results: Median settlements were 500, 000 and median verdict awards were 2, 000, 000. Postoperative negligence was alleged most often (81%) followed by intraoperative negligence (27.9%) and permanent injury (18.6%). Otolaryngologists were named as defendants most often (25.6%), with nurses named second most often. Pediatric cases had significantly higher awards and were more often named in favor of the plaintiff. Conclusion: An awareness of tracheotomy malpractice litigation has the potential to both help physicians avoid future litigation and improve patient safety. © 2015 Wiley Periodicals, Inc. Head Neck 38: 751–754, 2016